Real-Time Temperature Measurement Using Infrared Thermography Camera and Effects on Tensile Strength and Microhardness of Hot Wire Plasma Arc Welding - Nirut Naksuk; Jiradech Nakngoenthong; Waravut Printrakoon; Rattanapon Yuttawiriya (Metals, 2020)
The hot wire plasma arc welding process, a hybrid process between the plasma arc welding (PAW) process and hot wire process, is used to weld 316 stainless steel sheets, in which the temperature generated during welding is recorded in real time with a high-speed infrared thermography camera. Therefore, this research studies the factors in the hot wire process, of which there are two: (1) wire feed rate and (2) wire current; this study investigated the tensile strength, microhardness, and relationship of cooling rate per tensile strength and microhardness. The study found that the hot wire current plays an important role in cooling rates and tensile strength. The temperature results from high-speed infrared thermography camera show that the maximum welding temperature is around 1300 °C. The weld pool has a temperature between 900 and 1300 °C and the temperature profile of the weld pool will look like an “M” shaped, which is caused by the hot wire process. Finally, the appropriate hot wire parameters are 1.5 m/min for wire feed rate and 40A for wire current, which will give the workpiece cooling rate of 800–500 °C as 13.42 °C/s, tensile strength of 610.95 MPa, and the average Vickers microhardness of 195 HV.